Suture-free anastomosis of the colon. Experimental comparison of two cyanoacrylate adhesives - Paral, Jiri; Subrt, Zdenek; Lochman, Petr; Klein, Leo; Hadzi-Nikolov, Dimitar; Turek, Zdenek; Vejbera, Martin (Journal of gastrointestinal surgery, 2011)
BACKGROUND: We explored the potential of two cyanoacrylate tissue adhesives for constructing colonic anastomoses. METHOD: The study involved 12 female domestic pigs. The animals were divided into two equal groups. In both groups, the sigmoid colon was transected. An intestinal anastomosis was constructed with a modified circular stapler (all staples were withdrawn) and cyanoacrylate tissue adhesives. Glubran 2 was used in group A and Dermabond was applied in group B. Fourteen days after the first operation, a follow-up surgery was performed in both groups. The glued section of the colon was resected, processed with the standard paraffin technique and stained with haematoxylin-eosin. The finished specimens were examined under light microscopy. Assessments were made for the presence of fibroblasts, neutrophils, giant polynuclear cells, neovascularisation and collagen deposits. Adhesions, anastomotic dehiscence, peri-anastomotic inflammation and intestinal healing were assessed peri-operatively. RESULTS: All anastomoses in group A healed with no signs of pathology. In group B, fibrotic adhesions and stenoses tended to occur in areas surrounding the anastomoses. Histological examinations confirmed increased fibrosis. CONCLUSION: The tissue adhesive Glubran 2 appears to be (under experimental conditions) a promising synthetic adhesive for colonic anastomosis construction; conversely, the tissue adhesive Dermabond was unsuitable for suture-free anastomosis construction.
Keywords: Animals; zánět; Female; Tissue Adhesions; ženské pohlaví; Tissue Adhesives; Wound Healing; Surgical Wound Dehiscence; anastomóza chirurgická; prasata; dehiscence operační rány; tkáňová adheziva; kyanoakryláty; colon sigmoideum; Inflammation; adheze tkání; Anastomosis, Surgical; Swine; Cyanoacrylates; Colon, Sigmoid; hojení ran; zvířata